2020
DOI: 10.3389/fchem.2020.00179
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxysulfides: From Bulk Compounds to Nanomaterials

Abstract: This review summarizes the syntheses and applications of metal oxysulfides. Bulk compounds of rare earth and transition metals are discussed in the section Introduction. After a presentation of their main properties and applications, their structures are presented and their syntheses are discussed. The section Bulk Materials and Their Main Applications is dedicated to the growing field of nanoscaled metal oxysulfides. Synthesis and applications of lanthanide-based nanoparticles are more mature and are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 291 publications
0
47
0
Order By: Relevance
“…The analysis of the literature reveals that both oxides and oxysulphides systems have been used recently as contrast agents, detection agents, antimicrobial agents, transport systems (RNA, proteins, peptides, and drugs), and in the formulation of nanovaccines prototypes (see Table 1). Several authors agree that even despite a large number of nanoparticles available for these applications, the main attributes of gadolinium-based compounds make them attractive candidates [5]. In the last decade, the Gd 2 O 3 has been extensively used for biomedical applications, which is attributed to these reasons: (1) The easier production of Gd 2 O 3 than Gd 2 O 2 S, (2) the chemical modification of the Gd 2 O 3 surface is more accessible than Gd 2 O 2 S, and (3) the multifunctionality of Gd 2 O 3 as a contrast agent and therapeutic agent [122].…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the literature reveals that both oxides and oxysulphides systems have been used recently as contrast agents, detection agents, antimicrobial agents, transport systems (RNA, proteins, peptides, and drugs), and in the formulation of nanovaccines prototypes (see Table 1). Several authors agree that even despite a large number of nanoparticles available for these applications, the main attributes of gadolinium-based compounds make them attractive candidates [5]. In the last decade, the Gd 2 O 3 has been extensively used for biomedical applications, which is attributed to these reasons: (1) The easier production of Gd 2 O 3 than Gd 2 O 2 S, (2) the chemical modification of the Gd 2 O 3 surface is more accessible than Gd 2 O 2 S, and (3) the multifunctionality of Gd 2 O 3 as a contrast agent and therapeutic agent [122].…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
“…In the last decade, the Gd 2 O 3 has been extensively used for biomedical applications, which is attributed to these reasons: (1) The easier production of Gd 2 O 3 than Gd 2 O 2 S, (2) the chemical modification of the Gd 2 O 3 surface is more accessible than Gd 2 O 2 S, and (3) the multifunctionality of Gd 2 O 3 as a contrast agent and therapeutic agent [122]. However, advances in the synthesis methods have allowed a decrease in the particle size and modulation of the shape of the Gd 2 O 2 S. In the same biomedical applications, better results are expected due to the superior optical properties [5].…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work reported in Reference 64 showed that residual Cu (0.14 wt pct) has been found to combine with S (0.043 wt pct) to form CuS, which precipitates on existing MnS inclusions. More recently, a detailed review of metal oxysulfides was published by Larquet and Carenco, [65] in which it was reported that, Cu can form several oxysulfides such as Cu 2 O 1Àx S x , Sr 2 Cu 2 M-nO 2 S 2 , and Sr 2 CuMO 3 S (M = Sc, Cr, Fe).…”
Section: Hip'd 316l and 17-4ph Stainless Steelsmentioning
confidence: 99%
“…Among rare earth-based optical materials, rare earth oxysulfides RE2O2S (RE 3+ : La, Gd, Y and Lu) are suitable host lattices for luminescent materials due to their high thermal and chemical stability, low toxicity, and good sensitization of trivalent lanthanoid ions (Ln 3+ ), yielding high luminescence efficiency. The latter characteristic allows RE2O2S be versatile optical hosts, meaning that diverse luminescence phenomena can be obtained by tuning the host and dopant composition [12][13][14][15]. However, there are still some challenges and open questions regarding these materials.…”
Section: Introductionmentioning
confidence: 99%